Propagandowe wykorzystanie świąt i rocznic w okresie stalinowskim (1945-1956) na przykładzie regionu dolnośląskiego i częstochowskiego = Propaganda use of holidays and anniversaries in the Stalinist period (1945-1956) on the example of the lower Silesia and Częstochowa regions - Talarek, Adrian (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
After World War II, by virtue of arrangements made in Yalta and then in Potsdam, Poland found itself in the Soviet sphere of influence. Changes that took place in Poland after the Second World War also required a shift in state power. The period from 1945 to 1956 - the Stalinist period - can be described as the first phase of People`s Poland, although the name of the state was only changed to the Polish People`s Republic in 1952, after the adoption of the Polish People`s Republic constitution.
Keywords: propaganda; obchody; 1 Maja; 22 Lipca; pochód; dolnośląskie; Częstochowa (region); feast; 1 May; 22 July; parade; Lower Silesia; Częstochowa area